Political activists hanged by the government of India. - South Asian Students Association:::Creator::::::::::::
The pamphlet, which was printed and distributed by South Asian Students Association of University of California in Berkeley, criticizes the violent oppression of the Indian government against political dissent by highlighting the executions of political activists G. Kishtagoud and J. Bhoomiah on December 1st, 1975.